NEOLIBERAL REFORM IN BRAZILIAN PRIMARY HEALTH CARE: A CRITICAL ANALYSIS OF THE DISMANTLING OF THE NASF AND THE PRECARIOUSNESS OF EMULTI TEAMS - Tomim, Geiciely Cavanha (Seven Editora, 2025)
This study critically examines the impacts of transitioning from Family Health Support Centers (NASF) to multiprofessional teams (eMulti) in Brazilian Primary Health Care (PHC), focusing on psychosocial care dimensions, matrix support, and labor conditions. Utilizing a mixed-methods approach, we conducted: (1) documentary analysis of 53 normative instruments and government reports, (2) integrative literature review of t127 indexed publications (2008-2024), and (3) secondary data analysis from DATASUS and CNES national health information systems. The results reveal progressive systemic destabilization: a 38.7% reduction in federal funding allocated to eMulti teams, surge in professional turnover reaching 58.3% (compared to 12.1% under NASF model), and 73.2% decline in matrix support meetings. Concurrently, we observed a 133% increase in psychotropic prescriptions and weakening of Psychosocial Care Networks (RAPS) in 68% of analyzed municipalities. We conclude this transition represents a paradigmatic reorientation of PHC, aligned with neoliberal principles, characterized by: (1) precarious labor relations; (2) medicalization of psychological distress; and (3) erosion of expanded clinical practice principles. The findings underscore the urgent need for public policies that restore interprofessional collaboration as a structural axis, ensure permanent funding, and strengthen territorialized care practices. DOI: https://doi.org/10.56238/sevened2025.029-015